LIRAGLUTIDE 3.0 mg AS AN ADJUNCT TO INTENSIVE BEHAVIOR THERAPY IN INDIVIDUALS WITH OBESITY: SCALE IBT 56-WEEK RANDOMIZED, DOUBLEBLIND, PLACEBO-CONTROLLED TRIAL - Wadden, Thomas; Tronieri, Jena Shaw; Sugimoto, Danny; Lund, Michael Taulo; Auerbach, Pernille; Jensen, Camilla; Rubino, Domenica; Pasamba, Cyrus Q. (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION This 56-week, randomized, double-blind study investigated the effects of liraglutide 3.0 mg vs placebo, as adjunct to intensive behavior therapy. (IBT) and 23 counseling sessions. This reported the effects of treatment on weight change (co-primary endpoints: mean change in body weight [%] and proportion of individuals losing ≥5%), glycemic variables, cardiometabolic risk factors, safety and tolerability. Individuals aged ≥18 years with a body mass index (BMI) ≥30 kg/m2 and without diabetes were randomized 1:1 to liraglutide 3.0 mg or placebo along with IBT. METHODOLOGY Continuous and categorical variables were calculated using analysis of covariance (ANCOVA) and logistic regression respectively, with treatment, gender and BMI as factors and baseline endpoint as a covariate. Missing values were handled using a jump-to-reference multiple imputation model. RESULTS There were 282 individuals in the full analysis set; 142 were randomized to liraglutide 3.0 mg (45 y, 16% male, 109 kg, 39 kg/m2 ) and 140 to placebo (49 y, 17% male, 107 kg, 39 kg/m2 ); 99% and 93% completed the trial, respectively. The intention to treat analysis demonstrated weight loss at 56 weeks of 7.5% with liraglutide 3.0 mg and 4.0% with placebo (estimated treatment difference (ETD) [95% CI], 3.5% [5.3, 1.6]; p=0.0003). Weight loss in individuals on trial product at 56 weeks was 9.1% (n=114) and 4.8% (n=103), respectively. The proportion of individuals achieving ≥5% weight loss was 61.5% with liraglutide 3.0 mg and 38.8% with placebo (estimated odds ratio (OR) 2.5 [1.5, 4.1], p=0.0003). The proportion who lost >10% was 30.5% and 19.8% (OR 1.8 [1.01, 3.1], p=0.0469), and >15% was 18.1% and 8.9% (OR 2.3 [1.1, 4.7], p=0.0311, respectively. Change in waist circumference was -9.4 cm with liraglutide 3.0 mg vs -6.7 cm with placebo (ETD -2.7 cm [-4.7, -0.8], p=0.006). Significant improvements at 56 weeks were seen for liraglutide 3.0 mg vs placebo in both HbA1c (ETD -0.10% [-0.16, -0.04], p=0.0008) and fasting plasma glucose (ETD ‑0.23 mmol/L [-0.36, -0.11] p=0.0002). Blood pressure (BP) reductions were observed in both treatment arms at 56 weeks, but there were no significant differences between groups in systolic (ETD -2.2 mmHg [‑4.9, 0.5], p=0.11) or diastolic BP (ETD -0.2 mmHg [‑2.2, 1.8], p=0.87), or heart rate (ETD 1.3 bpm [-0.8, 3.4], p=0.23). Lipids were improved vs baseline but no significant differences between treatment arms were observed at 56 weeks (all p>0.05). CONCLUSION Liraglutide 3.0 mg was generally well tolerated and no new safety signals were observed in this study. The most frequent adverse events were gastrointestinal (liraglutide 3.0 mg: 71%; placebo: 49%). In conclusion, liraglutide 3.0 mg as an adjunct to IBT resulted in significantly greater weight loss, as compared to IBT and placebo.